1996
DOI: 10.1080/10643389609388489
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate‐reducing bacteria

Abstract: The corrosion of sewers and the control of odor are the major operational and maintenance problems in wastewater collection systems. The generation of hydrogen sulfide and subsequent sulfuric acid results from microbially mediated reactions, by sulfate-reducing bacteria (SBR) and sulfide-oxidizing bacteria. This review covers pertinent information about sulfate reduction-induced problems in general and SBR in particular. Metabolism with respect to carbon, energy, and sulfur sources, ecology, growth factors (di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
0
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(166 citation statements)
references
References 81 publications
5
152
0
9
Order By: Relevance
“…The identification of the SRB, which are known to be involved in corrosion (Crombie et al, 1980;Hao et al, 1996;Lee et al, 1995;Pankhania, 1988), could be of great importance for the technical progress of the long-term CO 2 storage technique. Thus, our recent investigations showed that members of this group were able to rapidly and massively change the permeability of the injectivity in the near well bore area Würdemann et al, in prep.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the SRB, which are known to be involved in corrosion (Crombie et al, 1980;Hao et al, 1996;Lee et al, 1995;Pankhania, 1988), could be of great importance for the technical progress of the long-term CO 2 storage technique. Thus, our recent investigations showed that members of this group were able to rapidly and massively change the permeability of the injectivity in the near well bore area Würdemann et al, in prep.…”
Section: Discussionmentioning
confidence: 99%
“…vulgaris H. can be grown and manipulated in the laboratory with ease; thus, this strain has been established as a useful model for the study of SRMs and as a representative of the broadly distributed Desulfovibrio genus, which is found in a variety of habitats 7,[10][11][12][13][14][15] . Much of the past interest in SRMs has been focused on their involvement in biocorrosion of ferrous metal installations in the petroleum industry 16,17 and of concrete structures in wastewater collection systems 18,19 . More recent studies 20 have documented the potential of SRMs in the bioremediation of toxic heavy metals and ) as the terminal electron acceptor during the degradation of simple organic matter.…”
mentioning
confidence: 99%
“…pH value played an important role in the bioremoval of heavy metal from aqueous solution. Hydrogen ions can vigorously compete with Tl(I) for the adsorption sites and the bacteria activity would be suppressed by low pH [28]. In addition, low pH value was not suitable for bacteria production and thus may cause a decline in metals adsorption.…”
Section: Effect Of Ph On Tl Removalmentioning
confidence: 99%